Determination of optical properties of single crystal diamond substrates grown via welding-assisted microwave plasma enhanced chemical vapour deposition - Khyati Upadhyay; Abhay Dasadia; Sandip V. Bhatt; M. P. Deshpande (Functional Diamond, 2024)
Lab grown single crystal diamonds (SCDs) offer unrivalled hardness, a wide range of optical transparency, and supremely high thermal conductivity reliable materials to be a part of devices run at high frequency, temperature, and power. Effective synthesis techniques are essential in enhancing the potential applications of high-quality SCDs. This study aims to decrease the thermal contact resistance between diamond seeds and the molybdenum holder by utilizing welding material. Quality of grown diamond substrates (plates) were assessed by analysing optical properties through Raman, UV-Vis, and FT-IR spectroscopic methods. The findings revealed that the grown single-crystal diamonds have excellent transmittance (>70%) and absorption at 270 nm. Calculations also showed an average absorption coefficient of 1.1 cm−1, indicating the high quality of the grown SCDs with nitrogen impurities below 10 ppm. The absorption observed in the FTIR spectra, ranging from 1600 cm−1 to 2700 cm−1 with a peak at 2354.13 cm−1, is referred to as the “two phonon region,” which is a distinctive feature of the diamond phase.